Training in the practice of noninvasive brain stimulation: Recommendations from an IFCN committee. Issue 3 (March 2021) - Fried, Peter J.; Santarnecchi, Emiliano; Antal, Andrea; Bartres-Faz, David; Bestmann, Sven; Carpenter, Linda L.; Celnik, Pablo; Edwards, Dylan; Farzan, Faranak; Fecteau, Shirley; George, Mark S.; He, Bin; et al.
Highlights: The field of NIBS is expanding and adequate training for all NIBS practitioners is needed. Training should be matched to the responsibilities of Technicians, Clinicians, and Scientists. We define competencies and propose curricula for TMS and tES organized in Core knowledge, Safety/ethics, Basic Skills, and Advanced Skills. Abstract: As the field of noninvasive brain stimulation (NIBS) expands, there is a growing need for comprehensive guidelines on training practitioners in the safe and effective administration of NIBS techniques in their various research and clinical applications. This article provides recommendations on the structure and content of this training. Three different types of practitioners are considered (Technicians, Clinicians, and Scientists), to attempt to cover the range of education and responsibilities of practitioners in NIBS from the laboratory to the clinic. Basic or core competencies and more advanced knowledge and skills are discussed, and recommendations offered regarding didactic and practical curricular components. We encourage individual licensing and governing bodies to implement these guidelines.